2000
DOI: 10.1111/j.1528-1157.2000.tb00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy Surgery in Children with Tuberous Sclerosis Complex: Presurgical Evaluation and Outcome

Abstract: Summary:Purpose: Children with tuberous sclerosis complex (TSC) benefit from excisional surgery if seizures can be localized to a single tuber. We evaluated the role of noninvasive studies to localize the epileptogenic tuberhegion (ET/R) and the outcome of focal resection.Methods: We identified 21 children with TSC, ages 3 months to 15 years (mean 4.8 years). All had video-(electroencephalogram) EEG and magnetic resonance imaging (MRI) scans, and 18 also had ictal single photon emission-computed tomography (SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
161
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(173 citation statements)
references
References 27 publications
9
161
1
2
Order By: Relevance
“…18,33 However, the hyperperfused lesions were identified during the ictal acquisition. The patients in our series did not have clinically apparent seizures during or preceding perfusion imaging.…”
Section: Discussionmentioning
confidence: 99%
“…18,33 However, the hyperperfused lesions were identified during the ictal acquisition. The patients in our series did not have clinically apparent seizures during or preceding perfusion imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence supports the importance of the perituberal cortex in TSC (for reviews see [165,218] and [219]). Accordingly, although epilepsy surgery targeting tubers may result in seizure freedom, [216,220] some patients continue to have seizures after tuber resection and, in fact, cases of TSC patients becoming seizure-free after resection of nontuberal cortex have been reported [221] (for a review see [165]). …”
Section: Epileptogenesismentioning
confidence: 99%
“…However, a number of studies have established a role for ictal SPECT in the localization of epileptogenic regions in patients with tuberous sclerosis complex. Koh et al 21 found areas of hyperperfusion on ictal SPECT in 10 of 18 patients that corresponded to the region of seizure onset defined by scalp EEG. Another group used subtraction ictal SPECT coregistered to MRI in the evaluation of 6 patients with TSC.…”
Section: Novel Methods For Preoperative Evaluation In Tscmentioning
confidence: 99%